2017
DOI: 10.17576/mjas-2017-2103-07
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Hydroxyapatite From Bulk Seashells and Its Potential Usage as Lead Ions Adsorbent

Abstract: In the present work, hydroxyapatite (HAP) powder was successfully synthesized via the thermal decomposition and subsequent wet precipitation (with different experimental reaction times of 3, 5, 24, 48, and 72 hours of bulk seashells. We found that the reaction time during wet precipitation stage affected the physical and chemical properties of HAPs adsorbents. HAP synthesized with a reaction time of 48 hours showed the highest removal of Pb 2+ ions (99.1%) and is highly potential to be used as bio adsorbent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Tang et al (2022) reported that the maximum amount of Pb 2+ adsorbed was 8.0 × 10 −4 mol/g using Fe-Mn oxide-modified biochar [38]. Ariffin et al (2017) prepared hydroxyapatite from bulk shells for lead ion adsorption and reported that the adsorption equilibrium relationship followed the Langmuirtype and the saturated adsorption capacity was 74.63 mg/g (3.6 × 10 −4 mol/g) [39]. Harripersadth et al (2020) carried out the adsorption of Pb 2+ using eggshell and reported that the removal efficiency of Pb was constant (100% removal) in the range of pH 3-7, the equilibrium adsorption isotherm was well fitted to the Langmuir adsorption model, and the maximum adsorption density of Pb was 277 mg/g (1.33 × 10 −3 mol/g) [40].…”
Section: Adsorption Equilibrium Relationship Between Pb Ions and Surf...mentioning
confidence: 99%
“…Tang et al (2022) reported that the maximum amount of Pb 2+ adsorbed was 8.0 × 10 −4 mol/g using Fe-Mn oxide-modified biochar [38]. Ariffin et al (2017) prepared hydroxyapatite from bulk shells for lead ion adsorption and reported that the adsorption equilibrium relationship followed the Langmuirtype and the saturated adsorption capacity was 74.63 mg/g (3.6 × 10 −4 mol/g) [39]. Harripersadth et al (2020) carried out the adsorption of Pb 2+ using eggshell and reported that the removal efficiency of Pb was constant (100% removal) in the range of pH 3-7, the equilibrium adsorption isotherm was well fitted to the Langmuir adsorption model, and the maximum adsorption density of Pb was 277 mg/g (1.33 × 10 −3 mol/g) [40].…”
Section: Adsorption Equilibrium Relationship Between Pb Ions and Surf...mentioning
confidence: 99%